Caracterização molecular de variantes no gene JAK2 em pacientes com neoplasias mieloproliferativas crônicas BCR/ABL1 negativo - Torres, Dania Isamary Gutierrez (2022)
BCR/ABL1 negative chronic myeloproliferative neoplasms are clonal diseases caused by aberrant proliferation of hematopoietic cells in the bone marrow and excessive accumulation of mature blood elements in peripheral blood. Polycythemia vera, essential thrombocythemia and primary myelofibrosis are the most classic entities within this classification of hematological diseases, which have in common genetic rearrangements in one of the main intracellular signaling pathways: the JAK2/STAT5 pathway. The JAK2 gene encodes the Janus kinase 2 (JAK2) protein, involved in cell proliferation and differentiation processes. JAK2V617F is the most frequent and most studied variant in this group of diseases due to its ability to generate several clinical phenotypes. Variants on exon 12 of the JAK2 gene are screened in JAK2V617F negative individuals, comprising approximately 3% of cases. Although JAK2V617F and JAK2 exon 12 variants are the main research targets in BCR/ABL1 negative Chronic Myeloproliferative Neoplasms, new variants throughout the gene have been identified. Objective: The study aimed to molecularly characterize variants in the JAK2 gene in patients with BCR/ABL1 negative Chronic Myeloproliferative Neoplasms: Polycythemia vera, Essential Thrombocythemia and Myelofibrosis. Methodology: We evaluated 75 patients diagnosed with BCR/ABL1 negative myeloproliferative neoplasms: Polycythemia vera, Essential Thrombocythemia and Myelofibrosis. Clinical data were obtained from medical records. Laboratory data were obtained from sample collections during the follow-up of subjects. Molecular evaluation was performed using conventional Polymerase Chain Reaction and Sanger Sequencing to detect variants in the coding region of the JAK2 gene. Statistical analysis of categorical variables was performed using the Chi-Square test. Kruskal-Wallis and Mann-Whitney tests were used to analyze numerical variables, when convenient. p <0.05 values were considered statistically significant. Results: Sanger sequencing demonstrated the presence of rs907414891, rs2230722, rs2230723, rs10119726, rs576746768, rs77375493 (JAK2V617F), rs2230728, rs2230724, rs41316003 and rs55930140 in the coding region of the JAK2 gene, considering rs77375493 the most frequent variant in individuals with Polycythemia vera. Coexistence of variants was detected in Polycythemia vera and Thrombocythemia, with the combination of variants rs2230722/rs77375493/rs2230724 being the most predominant in both hematological diseases with evidence of alterations in hematological parameters. Conclusions: Individuals with BCR/ABL1 negative chronic myeloproliferative neoplasms with the rs2230724, rs2230722 and rs77375493 variants both separately and together show slight alterations in the clinical-laboratory profile, especially in concomitance with the rs77375493 variant, demonstrating involvement in the instability of regulatory mechanisms at the protein level and possibly the myeloproliferative phenotype